2002
DOI: 10.1212/wnl.58.12.1809
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and cytogenetic analysis in leukocytes of Parkinson’s disease patients

Abstract: There is chromosomal, primary DNA damage and oxidative DNA damage demonstrable in lymphocytes of patients with untreated PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(76 citation statements)
references
References 56 publications
5
70
0
1
Order By: Relevance
“…There is a plethora of clinical and experimental data indicating that oxidative cell damage attributable to either ROS or NOderived reactive species is central to PD and other neurodegenerative diseases (Perry and Yong, 1986;Dexter et al, 1987;Sofic et al, 1991;Alam et al, 1997;Pearce et al, 1997;Knott et al, 2000;Migliore et al, 2002;Kunikowska and Jenner, 2003). In recent years, several genetically engineered mouse lines have been examined for their ability to model the pathology of PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a plethora of clinical and experimental data indicating that oxidative cell damage attributable to either ROS or NOderived reactive species is central to PD and other neurodegenerative diseases (Perry and Yong, 1986;Dexter et al, 1987;Sofic et al, 1991;Alam et al, 1997;Pearce et al, 1997;Knott et al, 2000;Migliore et al, 2002;Kunikowska and Jenner, 2003). In recent years, several genetically engineered mouse lines have been examined for their ability to model the pathology of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Selective decreases in reduced glutathione (GSH) (Perry and Yong, 1986;Pearce et al, 1997), mitochondrial complex I activity (Parker et al, 1989;Schapira et al, 1990;Tieu et al, 2004) and reactive oxygen species (ROS)-destroying enzymes (Kunikowska and Jenner, 2003) or elevated concentrations of iron, which can act as a catalyst for detrimental oxidative reactions (Dexter et al, 1987;Sofic et al, 1991), have been reported within the parkinsonian SN. In addition, there is evidence of oxidative damage to lipids, proteins, and DNA in the brains and leukocytes of PD patients (Alam et al, 1997;Migliore et al, 2002). Inflammatory-related events, such as nitric oxide (NO)-derived reactive species produced by glial inducible NO synthase (iNOS), appear also to participate in SN dopaminergic degeneration (Liberatore et al, 1999;Chung et al, 2004;Yao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in oxidative damage to DNA was also reported in leukocytes, serum, and CSF of PD patients Migliore et al, 2002). An increase in 3-nitrotyrosine immunoreactivity was reported in Lewy bodies in PD .…”
Section: Oxidative Damage In Pdmentioning
confidence: 82%
“…Moreover, the accelerated metabolism of dopamine by monoamine-oxidase-B may induce an excessive formation of hydrogen peroxide, superoxide anions, and hydroxyl radicals, which not only maintain the oxidative stress level, but also initiate/propagate apoptosis of the dopaminergic neurons [76]. According to the reports in the pertinent literature, Parkinson's disease is associated with increased oxidative damage to DNA [77], proteins [78] and lipids [79].…”
Section: Parkinson's Diseasementioning
confidence: 99%